THE POTENTIALS OF HISTORY STUDIES IN WAN YAHYA BIN WAN MOHD TAIB NOTE ABOUT THE 1914 MUSLIM PILGRIMAGE OF HAJJ MISSION - Mohd Kasri bin Saidon; Ishak Saat (Journal of Islamic, Social, Economics and Development, 2018)
This paper focuses on the personal record of a Kedah state chiefnamed Dato 'Hj Wan Yahya bin Wan Mohd Taib on his journey to the holy land. This entrywas the first in Kedah that wrote about the pilgrimage process and its whole experience. Hiswritings are narrative but there are some aspects that touch on an analytical basis. His note ismore complete and comprehensive than Abdullah Munshi's writings and is a rather detaileddescription of the journey of the pilgrimage to Mecca. Both of these writings are quitecomplete and comparable. Wan Yahya focuses more on the initial process ofpilgrimage and later give his commentary on the journey to the holy land. The note that heVolume: 3 Issue: 11 [June, 2018] pp.1-12]Journal of Islamic, Social, Economics and DevelopmenteISSN: 0128-1755Journal website: www.jised.com2wrote brings potential for further research for historians, not just in Malaysia but this note isalso worthy to Saudi Arabia. Many of the things that he touched have now become history andwhat is noted will be a more extensive research generation capital.